2016
DOI: 10.1080/13880209.2016.1199042
|View full text |Cite|
|
Sign up to set email alerts
|

Silymarin improved diet-induced liver damage and insulin resistance by decreasing inflammation in mice

Abstract: Context: Silymarin is the main flavonoid extracted from milk thistle, which has been used to treat liver diseases. Objective: The in vivo effect of silymarin on HFD-induced insulin resistance and fatty liver in mice was studied. Materials and methods: Male C57BL/6 mice were fed with high-fat diet (HFD) to induce obesity and insulin resistance and treated with 30, 60 mg/kg silymarin for 18 days. Food intake, body weight and the content/histology of epididymal fat and liver tissue were examined; the content of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…It has been found that silymarin as a safe and well‐tolerated dietary food supplement can protect against liver damages, reducing blood glucose and cholesterol in type 1 diabetic‐like diseases in rats (Cheng et al, ) and type 2 diabetes in patients (Huseini et al, ). It also has beneficial effects for obesity‐related hyperglycemia and insulin resistance by its antioxidant (Feng et al, ), anti‐inflammatory effect, reducing fat accumulation (Guo et al, ), body weight gains, and glucose tolerance (Feng et al, ) and also increasing β cells regeneration and insulin gene expression (Soto, Raya, Pérez, et al, ) and so on.…”
Section: Effect On Diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that silymarin as a safe and well‐tolerated dietary food supplement can protect against liver damages, reducing blood glucose and cholesterol in type 1 diabetic‐like diseases in rats (Cheng et al, ) and type 2 diabetes in patients (Huseini et al, ). It also has beneficial effects for obesity‐related hyperglycemia and insulin resistance by its antioxidant (Feng et al, ), anti‐inflammatory effect, reducing fat accumulation (Guo et al, ), body weight gains, and glucose tolerance (Feng et al, ) and also increasing β cells regeneration and insulin gene expression (Soto, Raya, Pérez, et al, ) and so on.…”
Section: Effect On Diabetesmentioning
confidence: 99%
“…A study on male mice received high fat diet suggested that positive effect of silymarin on obesity‐induced insulin resistance could be related on both anti‐inflammatory and fat mitigation effects (Guo et al, ). Another study demonstrated that treatment by silymarin in partially pancreatectomized rats can increase serum insulin and normalized serum glucose and may improve the reduction of β pancreatic cells by increasing transcription factors such as Nkx6.1, which is involved in growth, differentiation, and function maintenance of β‐pancreatic, and also can increase insulin gene expression (Soto, Raya, Pérez, et al, ).…”
Section: Effect On Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…36 There have been flourishing studies into the efficacy of oral silymarin on insulin resistance and glucose intolerance in animal models of obesity induced by a high fat diet. [36][37][38] When doses of 30 and 60 mg kg −1 of body weight of silymarin were applied in mice, which had been put on a high fat diet, it significantly improved insulin resistance and obesity. Furthermore, silymarin had protective effect on high fat-induced hepatic injury, and markedly improved glucose tolerance.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…The criteria for the hepatic steatosis score were as follows [26]: Grade 0 -Normal lobular architecture with central veins and no obvious steatosis, inflammation or necrosis was observed.…”
Section: Histopathological Examinationmentioning
confidence: 99%